Baked red pepper (Capsicum annuum L.) powder flavor analysis and evaluation under different exogenous Maillard reaction treatment. (March 2021) - Song, Yuting; Du, Bofeng; Ding, Zhuhong; Yu, Yihong; Wang, Yi
Abstract: To improve pepper powder product flavor, headspace gas chromatography-ion mobility spectrometry (HS-GC-IMS) was used to detect flavor substances in pepper powder, including dried pepper powder, baked pepper powder (BPP) and Maillard treated pepper powder (MTPP). Fifty-three flavor compounds were identified, mainly comprising alcohols, esters, aldehydes, ketones, etc. Volatile organic compound type and content in BPP and MTPPs differed from dried pepper powder, with more types present in MTPPs than BPP. Partial least-squares discrimination analysis and principal component analysis were employed to identify relationships between flavor substances and sample type, and evaluate different exogenous Maillard's flavoring reaction affects. Dried pepper powder was positively related with most flavor compounds, and Maillard reaction substrate combinations of lysine-xylose, lysine-lactose, valine-fructose, and valine-xylose exhibited high correlation with several characteristic compounds, whereas no characteristic compounds exhibited high correlations in BPP. Thus, adding exogenous Maillard reaction substrate offers a mechanism to improve BPP flavor quality. Highlights: The highlights of this study are: 1. Enhanced the aroma of baked pepper powder with Maillard reaction. 2. Fingerprint of pepper powder was established by GC–IMS combined with PCA and PLS-DA. 3. Differences of flavor compounds in different pepper powder products were analyzed. 4. Effects of different Maillard reaction on volatile compounds were analyzed.